Designing "Metamolecules" for Photonic Function: Reduced Backscattering. Issue 12 (31st August 2020) - Deng, Tian-Song; Parker, John; Hirai, Yutaro; Shepherd, Nolan; Yabu, Hiroshi; Scherer, Norbert F.
Abstract : Metamaterials, subwavelength nanostructured materials, can exhibit novel optical properties such as a negative index of refraction. Dielectric core–nanoparticle satellite clusters, termed "metamolecules, " can have strong optical magnetic resonances in the visible wavelength range—a requirement to achieve negative refractive index materials. However, achieving the desired photonic properties is challenging due to limited control in forming the metamolecule structures. Here, polystyrene (PS) core–gold nanoparticle (AuNP) satellite metamolecules with highly ordered single layers (monolayers) of AuNPs are fabricated and single particle spectroscopy, electron tomography structural measurements, and electrodynamics simulations are conducted to study the photonic properties of metamolecules constituted of ≈100 AuNPs. The simulated and experimental spectra of the many metamolecules studied, including excitation with azimuthally and radially polarized light, are in excellent agreement. It is shown that the scattering properties of the metamolecules are dominated by the AuNPs near the "equator" of the cluster, and that backscattering is strongly suppressed when different multipolar modes (e.g., dipolar and quadrupolar) of electric or optical magnetic character have comparable intensity due to the π‐phase shift of their scattering. Both the optical excitation fields and the ordering of the nanoparticles within metamolecules affect their optical excitation and scattering properties, providing new insights into designing novel photonic metamaterials. Abstract : Herein, an approach is demonstrated that combines single particle spectroscopy with vector beams, electron tomography, particle localization, and electrodynamics simulations to study the optical properties of complex plasmonic metamolecules. These nano‐ordered metamolecules are found to exhibit reduced backscattering. These metamolecules will be good candidate building blocks of metasurfaces that exhibit reduced reflectivity, especially at shorter optical wavelengths.